2017
DOI: 10.4103/2229-516x.198522
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different phases of menstrual cycle on brainstem auditory evoked response

Abstract: Introduction:The change in the hormonal levels during the three phases of menstrual cycle, namely, menstrual phase (hormonal withdrawal), proliferative phase (estrogen peak), and secretory phase (progesterone peak), influences the conduction velocities in the central auditory pathways. Variable findings of brainstem auditory evoked response (BAER) have been reported during different phases of menstrual cycle by different researchers.Aim:To study the effect of different phases of menstrual cycle on BAER.Methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…To determine an appropriate sample size for the current study, reference was made to Battaet al [ 10 ] who reported significant difference in wave latency at peak V across the menstrual cycle, and to Hjelmervik et al [ 2 ] who reported significant difference in ear advantage under the forced-left attention. Apower analysis software (G*Power v3.1.9.2, Heinrich Heine University, Germany) was used to estimate the sample size for the power to reach 0.8.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine an appropriate sample size for the current study, reference was made to Battaet al [ 10 ] who reported significant difference in wave latency at peak V across the menstrual cycle, and to Hjelmervik et al [ 2 ] who reported significant difference in ear advantage under the forced-left attention. Apower analysis software (G*Power v3.1.9.2, Heinrich Heine University, Germany) was used to estimate the sample size for the power to reach 0.8.…”
Section: Methodsmentioning
confidence: 99%
“…Apower analysis software (G*Power v3.1.9.2, Heinrich Heine University, Germany) was used to estimate the sample size for the power to reach 0.8. Based on these two studies [ 2 , 10 ], a sample size larger than 15 was required to examine the effects of the menstrual cycle on measurements in ABR and dichotic listening simultaneously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggest that variations in ovarian hormones during the menstrual cycle may produce positive effects on a number of cognitive functions including tasks involving working memory, cognitive inhibition, and verbal memory [9]. The ovarian hormone variations also have been shown to affect the function of the auditory mechanism [16, 17, 18]. Together, estrogen and progesterone may directly affect steroid receptors in the cochlea and indirectly influence auditory function by modulating cochlear blood supply [17].…”
Section: Introductionmentioning
confidence: 99%
“…Together, estrogen and progesterone may directly affect steroid receptors in the cochlea and indirectly influence auditory function by modulating cochlear blood supply [17]. For example, Batta et al [18] reported significantly shorter latencies of auditory brainstem evoked responses when their participants were tested during the days of their menstrual cycles after ovulation. In contrast, Hu and Lau [14] reported longer latency times when their participants were tested during this same portion of the menstrual cycle.…”
Section: Introductionmentioning
confidence: 99%